Cardiac rehabilitation outcomes following a 6-week program of PCI and CABG Patients - Jelinek, Herbert F.; Huang, Zhaoqi; Khandoker, Ahsan H.; Chang, Dennis; Kiat, Hosen (Frontiers in Physiology, 2013)
Coronary artery events requiring intervention are associated with depressed cardiac autonomic function. Whether a 6-week cardiac rehabilitation (CR) differs in effectiveness in improving exercise capacity (6MWT), cardiorespiratory function (peakVO2) and autonomic function (HRV) following either cardiac bypass surgery (CABG) or percutaneous coronary revascularization (PCI) is unknown. The current study therefore compared the change in 6MWT and peak VO2 to HRV variables following a 6-week cardiac rehabilitation program and with patients having either PCI or CABG. Thirty-eight patients, (PCI, n=22 and CABG, n=16) participated in the CR program and results for pre and post six minute walk test (6MWT), peakVO2 and heart rate variability (HRV) were obtained. Our study has shown that a six weeks program following either PCI or CABG improves function. However the effect on post-CABG differs to that of post-PCI patients. The change in distance walked (6MWT, metres) was higher in the CABG (Δ6MWT: 61, p